A Case of Descending Necrotizing Mediastinitis in a Previously Healthy Child - Toshihiko Okumura; Nobuyuki Tetsuka; Makoto Yamaguchi; Takako Suzuki; Yuka Torii; Jun-ichi Kawada; Yoshinori Ito (Hindawi Limited, 2021)
Descending necrotizing mediastinitis (DNM) is a rare complication of oropharyngeal and cervical infection, especially in children. We report a case of DNM secondary to a cervical abscess in a previously healthy 1-year-old boy. The patient presented with redness and swelling of the neck and fever. He was treated with an antimicrobial agent for the diagnosis of cervical lymphadenitis. On the sixth day, a huge mediastinal abscess was found, and he was admitted to the intensive care unit. He was successfully treated with surgical drainage and appropriate antimicrobial therapy. The pus culture isolated multiple bacteria, including methicillin-resistant Staphylococcus aureus (MRSA). Although we did not use an antimicrobial agent covering MRSA, the symptoms and test results improved. Washing with drainage was effective. The patient required multidisciplinary treatment, and we collaborated with specialists in other departments. DNM is a severe disease in which team medical care is needed to provide appropriate treatment.